PERANCANGAN CHASSIS TYPE TUBULAR SPACE FRAME UNTUK KENDARAAN LISTRIK - Tito Shantika; Eka Taufiq Firmansjah; Ilham Naufan (Jurnal Ilmiah Teknik Mesin POROS, 2018)
Abstract: Vehicle is the important think to get the better live for peoples of sociaty. Currently the development of vehicles is increasing rapidly, especially vehicles that use friendly energy for enviroment such as electrical energy. The electric vehicles have been used for commercial cars as well as for competitions. The race vehicle is required to develop new technologies in the particular vehicle. The electrical Vehicle Researces has been carried out include the systems such as drive train, Cassis, frame, batree, system control etc, however in this paper will be discuss design of electric vehicles Frame for Competition. The proces design will be accordance with the rules competition, there is dimensions, weight, power of vehicle etc. the vehicle specification requarenment will be created concept design, then embodiment design and detail design, theres will be figure out the strength and ergonomics frames to satisfy the safety criteria. Results of design obtained dimensions of frame 1800x800x1000 mm, 35.7 kg of weight, and material frame JIS G 3445 STKM 11 is obtained for static load load while stress of maximum impact load is 91.6 Mpa, deflection 0.61 mm and safety factor 2, 1.